PEDULI SARAPAN DAN JAJANAN SEHAT, SERTA HIGIENE DAN SANITASI LINGUNGAN SEKOLAH PADA SISWA SEKOLAH DASAR DI KECAMATAN SEPATAN TIMUR - Angkasa, Dudung; Sitoayu, Laras; Fauzi, Maulana; Putri, Vina Rizky; Mulyadi, Mulyadi (Universitas Esa Unggul, 2017)
AbstractSchool-aged children are among those vulnerable to nutritional problems. Irregular breakfast, unable to choose healthy snacks and poor personal hygiene are major factors in promoting nutritional problems among school-age children. Provision of nutritional and hygiene education is needed to improve students eating knowledge, attitudes and behavior as well as personal hygiene. Preliminary survey showed about 24.5% of students had underweight, 12.2% overweight based on BMI for age; Most students (92%) have a regular daily breakfast; however based on single 24 hours food recall, only 3%, 6.7%, 24.2% and 13.7% met energy, carbohydrate, protein and fat intake, respectively ; 54% of students have high snacking frequency (> 3x / day); small proportion of them consume vegetable (20%) and fruit (15%); proportion of student with poor personal hygiene about 28.4%. This activity was carried out in 14 primary schools in the working area of West Kedaung Community Health Center, East Sepatan, Tangerang District. A total of 1300 students from 14 schools were involved in this activity. The activity namely 1) nutrition counseling with the topics were: food guide, breakfast and healthy snacks which followed by pre-post test; 2) seven-step handwashing practice; 3) Personal hygiene practices; 4) distribution of educational posters; 5) a nutrition and seven-step dance hand washing contest. Results showed score increment for nutrition knowledge, breakfast and healthy snacks from 47.63 to 60.49; student were ablet to carry out a healthy meal, capable of performing seven handwashing steps, able to dispose of the garbage in its place, and the creation of a seven-step handwashing dance. Related to sanitation, the results of the activities show the improvement of school environment cleanliness such as toilets, yard, and classroom. However, only 10 out of 14 schools who progress to nutrition and seven-step handwashing dance creations contest. This activity should be continued to promote good eating and hygiene habits that can prevent nutritional problems in the future . Keywords: nutrition knowledge, breakfast, hand washing, sanitation, school children AbstrakAnak usia sekolah termasuk kelompok yang rentan terhadap masalah gizi. Tidak teratur sarapan, tidak mampu memilih jajanan sehat dan jeleknya hygiene individu merupakan faktor utama dalam mencentus masalah gizi pada anak usia sekolah. Pemberian pendidikan gizi dan hygiene diperlukan agar dapat meningkatkan pengetahuan siswa, memperbaiki sikap dan perilaku makan dan hygiene. Hasil survey pendahuluan menunjukkan sebanyak 24.5% siswa/i mengalami kurus+sangat kurus, 12.2% kegemukan berdasarkan IMT/U; sebanyak 92% memiliki kebiasaan rutin sarapan tetapi berdasarkan recall asupan 24 jam, hanya 3%, 6.7%, 24.2% dan 13.7% secara berturut yang cukup energi, karbohidrat, protein dan lemak; 54% siswa/i memiliki perilaku jajan yang tinggi (>3x/hari); asupan sayur dan buah masing-masing 20% dan 15% serta perilaku hygiene yang kurang sebanyak 28.4%. Kegiatan ini dilaksanakan di 14 sekolah dasar di wilayah kerja puskesmas Kedaung Barat, Sepatan Timur, Kabupaten Tangerang. Total 1300 siswa/i dari 14 sekolah terlibat dalam kegiatan ini. Kegiatan ini berupa penyuluhan tentang gizi, sarapan pagi dan jajanan sehat yang dilanjutkan dengan pre-post test; praktek tujuh langkah cuci tangan; praktek kebersihan dengan operasi semut; penyebaran poster; lomba cerdas cermat dan lomba tari tujuh langkah cuci tangan. Hasil pengabdian menunjukkan peningkatan skor pengetahuan gizi, sarapan dan jajanan sehat dari 47.63 menjadi 60.49, dibawanya bekal sehat, mampunya melakukan tujuh langkah cuci tangan, mampunya membuang sampah pada tempatnya, dan adanya kreasi tarian tujuh langkah cuci tangan. Terkait sanitasi, hasil kegiatan menunjukkan terlihatnya peningkatan kebersihan lingkungan sekolah seperti toilet, halaman, dan ruang kelas. Kekurangan dalam kegiatan ini iala saat puncak acara berupa lomba cerdas cermat dan kreasi tari hanya dapat diikuti oleh 10 sekolah. Harapannya, kegiatan ini terus dipromosikan sehingga terbentuk kebiasaan baik yang dapat mencegah masalah gizi dikemudian hari.Kata kunci: pengetahuan gizi, sarapan, cuci tangan, sanitasi, anak sekolah